2021
DOI: 10.33808/clinexphealthsci.655688
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Risk Assessment with Blood Parameters of The First Degree Relatives of Patients with Type-2 Diabetes Mellitus

Abstract: Objective: This study was conducted to evaluate the diabetes risk in first degree relatives of Type-2 diabetic patients who were not diagnosed with diabetes and test the validity of the Finnish Diabetes Risk Score (FINDRISK) in determining the risk of type-2 diabetes.Methods: First degree relatives of patients who were hospitalized in "İzmir Katip Çelebi University Atatürk Training and Research Hospital", who were not diagnosed with diabetes before, were included in this cross-sectional study. The sample of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Considering the risk of T2DM according to FINDRISC, 35 (5.8%) participants had a high risk of being diagnosed with diabetes within ten years. A study, which was conducted to assess the risk of diabetes in first-degree relatives of people with T2DM who were treated in hospital, found that 41.5% of individuals had a high and very high risk according to FINDRISC [8]. In [26], it was conducted a study with individuals aged between 35-75 in Sweden and found that 9.6% of the participants had a high-to-very high of diabetes, and 88.2% of these individuals had a family history of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the risk of T2DM according to FINDRISC, 35 (5.8%) participants had a high risk of being diagnosed with diabetes within ten years. A study, which was conducted to assess the risk of diabetes in first-degree relatives of people with T2DM who were treated in hospital, found that 41.5% of individuals had a high and very high risk according to FINDRISC [8]. In [26], it was conducted a study with individuals aged between 35-75 in Sweden and found that 9.6% of the participants had a high-to-very high of diabetes, and 88.2% of these individuals had a family history of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Screening individuals at risk and early recognition of the disease are essential to reduce the social burden of diabetes [8,9]. Additionally, the assessment of the risk perception of diabetes in family and close relatives of individuals with diabetes can contribute to disease prevention [10].…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the measure was the subject of a cohort study in 1992 (18). The Turkish validity and reliability study for FINDRISC was produced by Etbaş Demirağ (19) in 2016.…”
Section: The Findrisc Questionnairementioning
confidence: 99%